Corporate social responsibility disclosure of Indonesian Islamic banks - Sunarti Sunarti; Aris Eddy Sarwono (Proceeding of Conference on Islamic Management, Accounting, and Economics, 2018)
This study aims to analyze the influence of managerial ownership, gender, board composition and board's commitment to corporate social responsibility disclosure. The population of this research are Indonesian sharia banks in the period 2012-2017 . Sampling using purposive sampling, the number of samples is 9 sharia banks. Data was analyzed by Generalized Least Square with Random effect model approach. The results showed that managerial ownership had a negative effect on Corporate Social Responsibility Disclosure., The board composition and board comitmen had a positive effect on Corporate Social Responsibility disclosure. The gender has no effect on Corporate Social Responsibility disclosure.